Assistance in managing organic and non-organic waste in residential areas - Wilarso; Aswin Domodite; Asep Saepudin; Asep Dharmanto; Rudi Indrawan; Fauzi Ramdani (BEMAS: Jurnal Bermasyarakat, 2023)
Good management of organic and non-organic waste has an impact on comfort in residential areas and currently in the Cileungsi area, waste management has not been managed properly and has an adverse impact on the environment. As for housing, RT and RW environments, they are less active in terms of waste management. In the waste disposal process, each RT objected to the annual fee being increased. The fee charged for disposing of waste to the final shelter is around Rp. 12,500, - per head of family. It has been more or less 5 years since the levy fee has not been increased, due to the reason that the fee is used for other needs. Another problem also occurs in the Pesona Vista residential area, where garbage is collected by related parties, which takes 3-4 days each week. Under these conditions, discomfort arises in the environment, starting from the smell of garbage, because the rats eat the trash. The solution offered in this community service activity is organic and non-organic waste management to improve the economy of the community around the housing and create a healthy atmosphere in the housing environment. Organic waste will be managed to become liquid or solid compost. In the process of managing this organic waste using a counter, where there is a need for training on proper and correct operating and maintenance procedures. Meanwhile, plastic waste will be managed, to be sold to collectors